Teachers’ and Students’ Perspectives on the MBG Program: An Exploratory Study at SDN 16 Biau - Mohammad Safari; Mustakim; Saugadi (Madako Elementary School, 2026)
This study examines the suboptimal comprehensive understanding of the implementation of the Makan Bergizi Gratis (MBG) Program at the elementary school level, particularly from the perspectives of teachers and students. The aim of the study is to explore the dynamics of program acceptance, benefits, and challenges within the context of SDN 16 Biau. The method employed is qualitative with an exploratory study approach, involving the principal, teachers, and students as research subjects through interviews, observations, and documentation techniques. The findings indicate that, from the teachers’ perspective, the MBG program reflects a relatively effective adaptation process, supports the achievement of learning objectives, and is integrated into school activities, although latency in the form of technical constraints remains. From the students’ perspective, the program contributes to the fulfillment of physiological needs, a sense of safety, social interaction, esteem, and self-actualization. The level of program acceptance is considered positive with tangible benefits, despite challenges related to distribution and implementation consistency. These findings underscore the importance of continuous evaluation and strengthening of program management. The implication is that MBG has the potential to serve as a strategic intervention in enhancing students’ well-being and the overall quality of learning in a holistic manner.